Establishing participatory hydrological monitoring in the Nile BDC - McCartney, Matthew P. (International Livestock Research Institute, 2012)
In this video, Matthew McCartney (International Water Management Institute - IWMI) reflects on his work in the CPWF-funded Nile Basin Development Challenge (NBDC). He particularly focuses on the hydrological aspects and the establishment of primary monitoring stations at the three project sites.